2014
DOI: 10.1007/s11657-014-0177-0
|View full text |Cite
|
Sign up to set email alerts
|

Osteomalacia in Crohn’s disease

Abstract: Osteomalacia should be considered in differential diagnosis when assessing low back pain in the patients with chronic inflammatory bowel disease. Vitamin D deficiency should be treated with vitamin D supplementation in patients with Crohn's disease to prevent osteomalacia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Adequate calcium intake is crucial due to IBD’s association with an increased incidence of osteoporosis, and additionally, during ongoing inflammation, pro-inflammatory cytokines affect the activity of bone cells [ 42 ]. Due to impaired vitamin D absorption being associated with the disease, osteomalacia, which is associated with impaired bone mineralization, may also occur [ 48 ]. Studies by other researchers have also observed lower dietary calcium intake in patients with IBD [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adequate calcium intake is crucial due to IBD’s association with an increased incidence of osteoporosis, and additionally, during ongoing inflammation, pro-inflammatory cytokines affect the activity of bone cells [ 42 ]. Due to impaired vitamin D absorption being associated with the disease, osteomalacia, which is associated with impaired bone mineralization, may also occur [ 48 ]. Studies by other researchers have also observed lower dietary calcium intake in patients with IBD [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a pre-clinical study, mice with the absence of endothelial VDR expression displayed reduced bioavailability of NO due to impaired expression of the NO synthesizing enzyme, eNOS, within the endothelium (2). Similarly, when the endothelial-specific VDR was knocked out, reduction in eNOS expression and impaired ACh-induced vasorelaxation were observed in the aorta of mice [5].…”
Section: Effect Of Vitamin D On Regulation Of Nitric Oxide (No) Bioavmentioning
confidence: 99%
“…Data from the 2005-2006 National Health and Nutrition Examination Survey indicate that vitamin D deficiency, defined as a serum 25-hydroxyvitamin D levels ≤ 20 ng/mL (50 nmol/L), is common among adults aged 20 years and over in the United States (US), with 41.6% of adults reporting a vitamin D deficiency [1]. This vitamin D deficiency epidemic can be attributable to factors such as poor sunlight exposure, insufficient intake of vitamin-containing foods and malabsorption syndromes such as Crohn's disease and celiac disease [2].…”
Section: Introductionmentioning
confidence: 99%
“…Alternative sources of vitamin D3 include animal products, such as fatty fish, while vitamin D2 (ergocalciferol) can be obtained mainly from dietary plant and fungal sources such as mushrooms. Consequently, major risk factors for vitamin D deficiency include inadequate sunlight exposure, inadequate dietary intake of vitamin D-containing foods, and malabsorption syndromes such as Crohn’s disease and celiac disease [ 2 ]. Although clinically apparent manifestations of vitamin D deficiency, such as rickets in children or periosteal bone pain in adults, are uncommon in most developed countries, recent literature suggests that subclinical, asymptomatic vitamin D deficiency still plays a notable role in contributing to several of the leading causes of death, including cardiovascular disease, cancer, and diabetes.…”
Section: Introductionmentioning
confidence: 99%